A classification of meibomitis and an algorithm of its treatment - A. E. Sukhomlinov; V. I. Baranov; A. A. Kruchinina (Российский офтальмологический журнал, 2022)
Purpose. To develop a classification of meibomitis accounting for the diverse course and stages of progression and offer guidelines for treatment based on the algorithm proposed.Materials and methods. We observed 56 patients aged 4 to 68 (average age 33 years), of which 42 patients (75 %) were followed up for periods from 3 to 60 days. The patients received basic complex conservative treatment, probing the meibomian gland with an eyelash during the acute inflammation and microabscess stage, in the presence of the chalazion with and without inflammation manifestations, and underwent drainage of the microabscess or the chalazion according to the classification.Results. The proposed algorithm reduced the duration of meibomitis treatment. Relapses were only noted in 2 cases; one case was complicated by corneal erosion caused by hardened oil. No complications associated with the treatment have been noted and nobody was prescribed surgical removal of the chalazion.Conclusion. A meibomitis classification with effective combined treatment has been proposed, which is convenient for practitioners, cost-effective and not requiring special instruments or materials.